1979
DOI: 10.1172/jci109415
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Intrinsic Renal Tubular Defect in Mice with Genetic Hypophosphatemic Rickets

Abstract: A B S T R A C T To investigate the role of parathyroid hormone (PTH) and(or) an intrinsic renal tubular reabsorptive defect for phosphate in mice with hereditary hypophosphatemic rickets, we performed clearance and micropuncture studies in hypophosphatemic mutants and nonaffected littermate controls. Increased fractional excretion ofphosphate in mutants (47.2 +4 vs. 30.8+2% in controls) was associated with reduced fractional and absolute reabsorption in the proximal convoluted tubule and more distal sites. Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…These studies demonstrated that immunofluorescence was restricted to the brush border membrane of both the proximal convoluted tubule, where the signal was strongest, and the proximal straight tubule, where a weaker signal was obtained ( 17). Based on these findings, it is likely that the Na'-Pi cotransporter protein that is reduced in Hyp mice is expressed in the brush border membrane of both proximal tubular segments, consistent with results of renal micropuncture studies in intact mice (8,9) and Pi transport measurements in isolated renal brush border membrane vesicles (6,7).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These studies demonstrated that immunofluorescence was restricted to the brush border membrane of both the proximal convoluted tubule, where the signal was strongest, and the proximal straight tubule, where a weaker signal was obtained ( 17). Based on these findings, it is likely that the Na'-Pi cotransporter protein that is reduced in Hyp mice is expressed in the brush border membrane of both proximal tubular segments, consistent with results of renal micropuncture studies in intact mice (8,9) and Pi transport measurements in isolated renal brush border membrane vesicles (6,7).…”
Section: Discussionsupporting
confidence: 77%
“…The renal defect in Pi reabsorption in Hyp mice has been localized to the brush border membrane ofthe proximal tubule (6)(7)(8) and is not dependent on parathyroid hormone for its expression (9). Kinetic studies provided evidence for two distinct Na+-Pi cotransport systems in renal brush border membrane vesicles of Hyp mice (10).…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3. Indomethacin treatment resulted in a significant decrease in the FE PO 4 to levels comparable to that seen in C57͞B6 mice and a significant increase in serum phosphate compared with vehicle-treated Hyp mice. Indomethacin treatment did not affect the serum creatinine in either C57͞B6 or Hyp mice.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, there was a significant increase in serum phosphate, although not to levels of C57͞B6 mice. The question remains as to why indomethacin treatment resulted in a decrease in the FE PO 4 and an increase in serum phosphate in Hyp mice, while having no effect in C57͞B6 mice. There are several possible explanations: First, FE PO 4 in C57͞B6 mice was extremely low, and tubular transport may have been at a maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Further data supporting this possibility derives from previous studies demonstrating impaired adenylate cyclase response to PTH in the PCT of Hyp-mice (21). In addition, since defective phosphate transport in the Hypmice undoubtedly occurs in the PCT (22)(23)(24), the primary site of phosphate transport (25), it would not be surprising if this were the site of the abnormal vitamin D metabolism. Indeed, aberrant response of the PCT 25(OH)D-lIa-hydroxylase may result from abnormal phosphate transport and consequent changes in the intracellular milieu.…”
Section: Discussionmentioning
confidence: 91%